Topography, soil carbon-nitrogen ratio and vegetation in boreal coniferous forests at the landscape level - Chaminade, Guillermo (2006)
This thesis was developed with the main objective of assessing the mutual influence of three of the main factors taking part in the ecological processes of the boreal forest: topography and the hydrological fluxes related to it, C/N ratio in the forest soil, and vegetation composition. The interaction between these factors has not been the main focus in any study of this kind before, although in numerous reports these variables and their role in the forests have been assessed.